2020
DOI: 10.1177/1753193420927999
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of dorsal web space versus palmar midline injection of steroid in the treatment of trigger digits

Abstract: One hundred and sixty patients were enrolled in a prospective randomized controlled trial to assess whether a steroid injection through the dorsal web space was less painful than the palmar midline technique in the treatment of trigger digits and whether they were equally effective. There were 116 women and 44 men with a mean age of 60 years. The mean visual analogue score for pain during the injection was 3.6 in the dorsal web space group and 5.4 in the palmar midline group on a scale of 0–10. The overall suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…This is in keeping with previous literature on the use of ethyl chloride spray 48 . Jiménez et al 49 compared a technique of corticosteroid injection that utilized an approach from the dorsal web space into the area of the A1 pulley and the typical palmar midline technique. This study showed a significantly lower mean visual analog scale score for pain of 3.6 for patients who underwent the dorsal webspace technique compared with 5.4 for patients who underwent the palmar midline technique.…”
Section: Trigger Fingermentioning
confidence: 99%
“…This is in keeping with previous literature on the use of ethyl chloride spray 48 . Jiménez et al 49 compared a technique of corticosteroid injection that utilized an approach from the dorsal web space into the area of the A1 pulley and the typical palmar midline technique. This study showed a significantly lower mean visual analog scale score for pain of 3.6 for patients who underwent the dorsal webspace technique compared with 5.4 for patients who underwent the palmar midline technique.…”
Section: Trigger Fingermentioning
confidence: 99%
“…(2023) did not find a difference in pain experienced during the injection between the two sites. Jiménez et al. (2020) carried out a prospective RCT comparing steroid injection over the A1 pulley palmately and a dorsal web space injection site, both aiming to deliver steroid near to, but not into, the flexor sheath.…”
Section: Introductionmentioning
confidence: 99%
“…The first annular (A1) pulley is where the main triggering occurs, followed by compression and long-term friction obstructing the flexor tendon to glide in the fibrous sheath involving the thumb [ 3 ]. There have been various proven effective treatments (percutaneous needle [PN] release under local anesthesia with a 93% success rate, corticosteroid injections, and nonsteroidal anti-inflammatory drugs with an 85% success rate) to overcome this painful condition [ 4 , 5 ]. However, all cases could only be resolved partially [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…There have been various proven effective treatments (percutaneous needle [PN] release under local anesthesia with a 93% success rate, corticosteroid injections, and nonsteroidal anti-inflammatory drugs with an 85% success rate) to overcome this painful condition [ 4 , 5 ]. However, all cases could only be resolved partially [ 4 , 5 ]. The overall success rate ranges from 35% to 85% in the decrease in pain and triggering after corticosteroid injection [ 6 ].…”
Section: Introductionmentioning
confidence: 99%